65.5k views
4 votes
Consider the following functions.

f(x):y=3x-2 g(x):y=x^2-4 h(x):=2^x-1
In each of these functions, y is the dependent variable which “depends on” or “is in terms of x”. You will recall, to find the inverse of a function you switch the x and y variables, and then solve for x. The inverse function is designated with the -1 exponent as below.
f^-1(x):x=3y-2 g^-1(x):x=y^2-4 h^-1(x):x=2^y-1
You should be able to solve for the first two inverse functions using concepts you learned in Algebra One and Two. Go ahead and solve each inverse function for y. If you cannot solve the third one, describe why.

User Unbalanced
by
5.6k points

1 Answer

4 votes
Well this kinda hard I’ll work it out
User Faustino
by
5.7k points